Is Micronucleus Assay Suitable for Cytogenetic Biomonitoring the Different Ways to Smoke? - Daniel Ribeiro; Ingra Malacarne; Daniel Souza (Iranian Society of Pathology, 2020)
The aim of the letter to editor is to provide some comments regarding the manuscript of DehghanNezhad et al.(1) recently published in the Iranian Journal of Pathology titled "Micronucleus Assay of Buccal Mucosa Cells in Waterpipe (Hookah) Smokers: A Cytologic Study." In this article, the authors were able to detect high frequencies of micronucleus in buccal mucosa cells of waterpipe smokers when compared to non-smokers.